(untitled) (Journal of Civil Engineering Researchers, 2022)
Today, the use of processed mineral materials in concrete to improve mechanical properties and durability has opened a wide field of vision for researchers in the structural sciences. On the other hand, preserving the environment by reducing the toxic gas of carbon dioxide caused by cement production is one of the concerns of scientists. In this regard, minerals containing abundant aluminosilicate particles and active alkali solution (AAS) replaced ordinary cement in concrete and led to the production of geopolymer concrete (GPC). The composition and reactivity of these materials produce a strong adhesive material that in combination with other concrete components, causes the final strength of GPC. High temperatures weaken the concrete against loads by damaging the structure of hydrated gels in concrete. GPC has better fire resistance than OPCC due to its density in its microstructure. In the current study, Granulated Blast Furnace Slag (GBFS)-based GPC was used with 0-2% polyolefin fibers (POFs) and 0-8% Nano silica (NS) to improve its structure. After curing the specimens under dry conditions at a temperature of 60 °C in an oven, they were subjected to Compressive strength, Modulus of elasticity and Weight Loss tests to evaluate their mechanical properties. all tests were performed at 90 days of age under ambient temperature (20 ℃) and high temperature (500 ℃). The addition of NS enhanced the whole properties of the GBFS-based GPC. Addition of up to 8% NS to the GPC composition at 20% temperature improved the modulus of elasticity test results by 13.42% and the compressive strength up to 21.94% by 11.58%. Addition of up to 2% of POFs to the GPC composition resulted in an improvement, modulus of elasticity of 07.05% and a decrease in compressive strength of up to 22.49%. Apply the lowest (0.061%) and highest (0.12%) weight loss percentage of concrete samples under 500% heat, belonging to scheme 4 (including GPC containing 8% NS) and scheme 6 (including GPC containing 2% POFs) Came. In the following, by conducting the Slag, Scanning Electron Microscope (SEM) analysis, a microstructure investigation was carried out on the concrete samples. In addition to their overlapping with each other, the results indicate the GPC superiority over the regular concrete. Besides, it demonstrated the positive influence of NS addition on the concert microstructure.